The new girl [compact disc, unabridged] : a novel - Silva, Daniel, 1960- (Silva, Daniel, 1960- Gabriel Allon series., 2019)
At an exclusive private school in Switzerland, mystery surrounds the identity of the beautiful girl who arrives each morning and leaves each afternoon in a heavily protected motorcade fit for a head of state. She is said to be the daughter of a wealthy international businessman. She is not. And when she is brutally kidnapped across the border in the Haute-Savoie region of France, Gabriel Allon, the legendary chief of Israeli intelligence, is thrust into a deadly secret war with an old enemy that will determine the future of the Middle East and perhaps the world.